Preoperative Ketamine Gargle for Prevention of Postoperative Sore Throat After Tracheal Intubation in Adults: A Meta-Analysis - Saihao Fu; Mengrong Miao; Jing Bian; Yunxiang Fu; Jiaqiang Zhang; Mingyang Sun (Pain Research and Management)
Conclusion: Our meta-analysis demonstrated the efficacy of prophylactic ketamine gargle in reducing the incidence of POST across all studied time intervals in patients requiring tracheal intubation of general anesthesia compared to placebo.